Electrolyte engineering and interphase chemistry toward high-performance nickel-rich cathodes: Progress and perspectives - Shangjuan Yang; Ke Yang; Jinshuo Mi; Shaoke Guo; Xufei An; Hai Su; Yanbing He (Materials Reports: Energy)
Nickel (Ni)-rich layered oxides have drawn great attention as cathode for lithium batteries due to their high capacity, high working voltage and competitive cost. Unfortunately, the operation of Ni-rich cathodes suffers from the notorious structural degradation and interfacial side reactions with electrolytes and thus incurs premature failure, especially at high charge cut-off voltages (≥4.4 V). For this, various structural and interphase regulation strategies (such as coating modification, element doping, and electrolyte engineering) are developed to enhance the cycling survivability of Ni-rich cathodes. Among them, electrolyte engineering by changing solvation structure and introducing additives has been considered an efficient method for constructing robust cathode-electrolyte interphases (CEI), inhibiting the formation of harmful species (such as HF and H2O) or restraining the dissolution of transition metal ions. However, there is still an absence of systematic guidelines for selecting and designing competitive electrolyte systems for Ni-rich layered cathodes. In this review, we comprehensively summarize the recent research progress on electrolyte engineering for Ni-rich layered cathodes according to their working mechanisms. Moreover, we propose future perspectives of improving the electrolyte performance, which will provide new insights for designing novel electrolytes toward high-performance Ni-rich layered cathodes.